Microbial consumption of zero‐valence sulfur in marine benthic habitats. (27th February 2014) - Pjevac, Petra; Kamyshny, Alexey; Dyksma, Stefan; Mußmann, Marc
Summary Zero‐valence sulfur (S0) is a central intermediate in the marine sulfur cycle and forms conspicuous accumulations at sediment surfaces, hydrothermal vents and in oxygen minimum zones. Diverse microorganisms can utilize S0, but those consuming S0 in the environment are largely unknown. We identified possible key players in S0 turnover on native or introduced S0 in benthic coastal and deep‐sea habitats using the 16S ribosomal RNA approach, (in situ) growth experiments and activity measurements. In all habitats, the epsilonproteobacterial Sulfurimonas/Sulfurovum group accounted for a substantial fraction of the microbial community. Deltaproteobacterial Desulfobulbaceae and Desulfuromonadales were also frequently detected, indicating S0 disproportionation and S0 respiration under anoxic conditions. Sulfate production from S0 particles colonized in situ with Sulfurimonas/Sulfurovum suggested that this group oxidized S0. We also show that the type strain Sulfurimonas denitrificans is able to access cyclooctasulfur (S8), a metabolic feature not yet demonstrated for sulfur oxidizers. The ability to oxidize S0, in particular S8, likely facilitates niche partitioning among sulfur oxidizers in habitats with intense microbial sulfur cycling such as sulfidic sediment surfaces. Our results underscore the previously overlooked but central role of Sulfurimonas/Sulfurovum group for conversion of free S0 at the seafloor surface.